Methicillin resistant Staphylococcus aureus (MRSA) carriage among health care workers in a tertiary care hospital in Bhubaneswar - Singh, Nipa; Mohanty, Sourav; Panda, Subhra Snigdha; Sahoo, Smrutilata; Pattnaik, Dipti; Jena, Jagadananda (International Journal Of Community Medicine And Public Health, 2018)
Background: Methicillin resistant Staphylococcus aureus (MRSA) is a multidrug resistant organism emerging as a major cause of hospital acquired infection. In a healthcare setup a patient may acquire MRSA through the hands, clothes and equipments of health care workers. Screening of health care workers colonised with MRSA will be helpful in preventing the spread of this organism in a hospital. With this background the present study was undertaken to estimate the carriage rate of MRSA among healthcare workers in our hospital. Methods: Nasal swabs were collected from 120 health care workers working in Kalinga Institute of Medical Sciences (KIMS), Bhubaneswar during the study period of July- September 2017. The swabs were inoculated onto mannitol salt agar plates for isolation of Staphylococcus aureus. MRSA strains were identified by cefoxitin disc method. Antibiogram of MRSA strains was determined. Results: The prevalence of MRSA carriage among health care workers was 7.5% with the carrier rate being highest among nurses (10%). All the MRSA isolates were 100% resistant to penicillin. MRSA isolates were 90% resistant to amoxyclav, 60% to cotrimoxazole and erythromycin and 50% to clindamycin. Conclusions: Although the prevalence of MRSA among health care workers in our hospital is not alarming, it is important to emphasize the need for stringent hospital infection control policies to reduce the spread of MRSA to susceptible individuals.